Silk Fibroin: A Promising Tool for Wound Healing and Skin Regeneration - M. Vidya; Senthilkumar Rajagopal (International Journal of Polymer Science)
Silk is a functional protein biomaterial produced by a variety of insects like flies, silkworms, scorpions, spiders, and mites. Silk synthesized by silkworms is extensively studied for its applications in tissue engineering and wound healing. Silk is undoubtedly a natural biocompatible material with humans and has its role in medical treatments from ancient times. The silk worm protein comprises two types of proteins namely fibroin and sericin. Silk fibroin makes up approximately 70% of cocoon weight and has wide applications in textiles and in all biomedical applications owing to its biocompatible, nontoxic, biodegradable, less immunogenic, and noncarcinogenic nature. It possesses outstanding toughness and mechanical strength, while silk sericin possesses high defensive ability against ultraviolet light and oxidation. Silk fibroin has been known to induce wound healing by increasing cell proliferation and growth and migrating various types of cells which are involved in different stages of wound healing process. With several silk varieties like silk worm fibroin, silk sericin, recombinant silk materials, and native spider silk have been investigated for its wound healing applications over the last several decades. With an objective of harnessing the silk regenerative properties, plentiful strategies have been studied and applied to develop bioartificial skin grafts and bioactive wound dressings in recent times. This review gives a detailed insight into the structure, general properties, fibroin structure-properties relationship, and biomedical applications of silk fibroin.